Building digital governance ecosystem readiness for Indonesian regional representative council institution - Zahir, Lalu Niqman; Jati, Wasisto Raharjo (Otoritas : Jurnal Ilmu Pemerintahan, 2025)
The Regional Representative Council of the Republic of Indonesia (DPD RI) faces the challenge of digital transformation. This research evaluates its digital readiness, comparing it with Estonia, South Korea, Singapore, and India, to bridge the digital divide between the central office and regional offices. Using gap analysis, Multi-Dimensional Scaling (MDS), and the Analytical Hierarchy Process (AHP), we found that infrastructure, institutions, and human resources are key factors. The AHP prioritizes human resources (43.9%), institutions (31.1%), and infrastructure (19.6%). The top programs include i-Parliament Literacy (40.3%), i-Parliament Management (39.6%), and Digital Infrastructure (20.1%), which have the potential to increase the readiness index to 76.43 (“VERY READY”). Currently, the DPD RI index stands at 56.05 (“READY”), indicating significant regional disparities, particularly in Eastern Indonesia, and lagging behind benchmark countries in terms of interconnectivity, security, and parliamentary digitalization. This prioritizes “soft infrastructure” (80%) over “hard infrastructure” (20.1%), aligning with initiatives such as the Digital New Deal 2.0 and Digital India. This study validates and develops the combined application of gap analysis, MDS, and AHP.